2018
DOI: 10.1093/eurpub/cky126
|View full text |Cite
|
Sign up to set email alerts
|

Infectious and dermatological diseases among arriving migrants on the Italian coasts

Abstract: The majority of the diseases affecting migrants is in most cases, related to the migration experience and is likely not to represent a major threat for public health. Up-to-date information regarding the burden of diseases is needed in order to identify the health needs of incoming migrants and to arrange the appropriate response in terms of health services provision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…Further research is currently underway to explain the factors associated with transmission in these groups in Norway. In some European countries, migration and travel have been investigated as factors possibly associated with scabies [4,5,12], particularly in the context of screening of asylum seekers upon arrival and mass treatment of scabies in reception centers [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Further research is currently underway to explain the factors associated with transmission in these groups in Norway. In some European countries, migration and travel have been investigated as factors possibly associated with scabies [4,5,12], particularly in the context of screening of asylum seekers upon arrival and mass treatment of scabies in reception centers [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of global migration, body lice infestation is increasingly relevant in Europe and B recurrentis infection (relapsing fever) is seen in migrants from, or with close contact with individuals from, the horn of Africa. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Italian reception centres with newly arrived refugees [10] showed that the most frequent conditions are those related to the migration experience and not representing a major threat for public health, as scabies, skin and respiratory infections. All these studies highlight that the misinformation in this situation is high, and more research involving the real burden of diseases is needed in order to identify the health needs of incoming migrants to arrange the appropriate response in terms of health services provision.…”
mentioning
confidence: 99%